PENGARUH MINAT PERILAKU WAJIB PAJAK ORANG PRIBADI DAN EFEKTIVITAS E-FILING TERHADAP KEPATUHAN FORMAL PERPAJAKAN - Isnawati, Isnawati; Ahalik, Ahalik (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2024)
This research was conducted to examine or determine the impact of individual taxpayer behavior and the effect of electronic filing on employee taxpayer compliance (case study of PT. Kian Santang Muliatama staff). The decline in state tax revenue from taxes makes this a concern. This research is quantitative and uses a survey tool in the form of a questionnaire. Data collection used a convenience sampling method with an SPSS 21 application. The sample for this study was 70 respondents, the population in this study were employees registered at PT. Kian Santang Muliatama. The questionnaire was checked for validity and reliability before the study. The classic hypothesis test used is the normality test, multicollinearity test and variance of variance test, as well as the t test and F test. The results of this study indicate that the interest in individual taxpayer behavior and e-filing effectiveness affect taxpayer compliance.